Long‐Term Academic Outcomes of Triological Society Research Career Development Award Recipients. (5th May 2020) - Dorismond, Christina; Prince, Andrew C.; Farzal, Zainab; Zanation, Adam M.
Abstract : Objectives/Hypothesis: Each year, the Triological Society awards several Research Career Development Awards (CDAs) to support early‐career otolaryngologists. The objective of this study was to evaluate academic outcomes of CDA recipients including National Institutes of Health (NIH) funding acquisition and h ‐index. A secondary objective was to appraise gender differences in outcomes among awardees. Study Design: Cross‐sectional study. Methods: Recipients' practice setting, degree type, academic rank, and leadership titles were determined through review of academic and private practice profiles in October 2019. NIH funding was assessed using the NIH Research Portfolio Online Reporting Tool and the h ‐index was calculated using the Scopus database. Results: Between 2004 and 2019, 70 investigators received a CDA. Of the 65 awardees prior to 2019, 26 (40.0%) obtained NIH grants after the CDA. Having an MD/PhD or MD/master's was not associated with NIH funding attainment ( P = .891) nor with higher funding total ( P = .109). However, funding total was significantly higher for full professors compared to assistant professors ( P = .022). The median h ‐index among awardees was 16 (interquartile range = 11–21) and differed significantly by academic rank ( P < .001). Moreover, 23 CDAs (32.9%) were awarded to women. However, fewer female recipients obtain NIH funding after the CDA compared to men (10.5% vs. 52.2%, P = .002), and they had significantly lower h ‐indices than men (10 vs. 17, P < .001). Conclusions: As a cohort, CDA awardees achieve higher academic success than academic otolaryngologists in general. However, female CDA recipients lag behind their male colleagues, highlighting the need for more research to uncover contributors to gender differences and ways to foster equity in research. Level of Evidence: NA Laryngoscope, 131:288–293, 2021